Aerogel powder manufacturing method and heat insulating material using the same

The production of weakly bonded ultrafine airgel powder with a three-dimensional network structure addresses the cost and brittleness issues of silica-based aerogels, achieving cost-effective and efficient thermal insulation.

JP7607955B2Active Publication Date: 2025-01-06NAT INST FOR MATERIALS SCI
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022563561
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-20
Filing Date
2021-06-04
Publication Date
2025-01-06
Estimated Expiration
2041-06-04

AI Technical Summary

Technical Problem

Silica-based aerogels are expensive and brittle, limiting their practical applications, and there is a need for a cost-effective, mechanically robust aerogel suitable for insulation and low-temperature liquid storage and transport.

Method used

A method for producing weakly bonded ultrafine airgel powder involves mixing metal alkoxides with solvents, hydrolyzing, gelling, aging, modifying the network structure, and pulverizing to create a three-dimensional network structure with primary particles as the skeletal unit, optionally hybridized with hollow particles to enhance insulation properties.

Benefits of technology

The method reduces production costs and enhances thermal insulation by increasing the volume occupied by the airgel powder with the same weight, while maintaining excellent heat insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607955000004
    Figure 0007607955000004
  • Figure 0007607955000005
    Figure 0007607955000005
  • Figure 0007607955000006
    Figure 0007607955000006
Patent Text Reader

Abstract

A method for manufacturing aerogel powder according to the present invention comprises: a mixing step for mixing and hydrolyzing silicon alkoxide (tetraethoxysilane (TEOS)) and a solvent (methanol) so as to generate a sol; a gelling step for gelling the sol obtained in the mixing step; an aging step for aging the gel obtained in the gelling step so as to obtain a wet gel (alcogel); a solvent replacement step for replacing the solvent for the wet gel with a prescribed solvent for replacement (hexane); a modification step for using TMCS to modify the surface of a mesh structure of the wet gel with a prescribed organic group; a step for washing the modified wet gel obtained through the wet gel production process; a step for drying the washed modified wet gel; and a step for crushing the dried washed modified wet gel. The present invention makes it possible to reduce manufacturing costs per unit occupied volume and to provide aerogel powder that has excellent heat-insulating properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat insulating material using aerogel and a method for producing the same, and in particular to a method for producing weakly bonded ultrafine aerogel powder, a method for producing weakly bonded ultrafine aerogel powder hybridized with hollow particles, and a heat insulating material using them. [Background technology]

[0002] Aerogel is a material that was first described in 1931 (Non-Patent Document 1) and is generally defined as a gel consisting of a microporous solid with a gas as the dispersed phase.

[0003] Although aerogels are very low density materials, they are delicate, fragile and very fragile, which makes them difficult to apply in many practical situations. Therefore, new types of mechanically robust aerogels are needed for engineering applications such as novel filters, highly insulated windows, ultra-thin walls for refrigerators, and high insulation in buildings. To achieve this goal, hybrid aerogels reinforced with fibers and other organic molecules have been studied. For example, it has been proposed to modify the surface of silica aerogel with organic groups and to produce a low-density porous structure by natural drying, which is comparable to aerogels produced by supercritical drying. Moreover, Patent Documents 1 and 2 propose an aerogel composite that has not only heat insulating properties but also flexibility.

[0004] However, aerogels suitable for many practical applications have not yet been developed. In particular, aerogels produced by supercritical drying are expensive, and the price factor is also an obstacle to practical applications. On the other hand, the storage and transportation of cryogenic liquids, such as liquid hydrogen and liquid helium, which have lower boiling points (-252.8°C for liquid hydrogen) compared to the boiling point of liquid nitrogen (-196°C), is becoming increasingly important. Therefore, the development of aerogels suitable for the storage and transportation of cryogenic liquids such as liquid hydrogen and liquid helium is anticipated. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2017 / 170498 publication [Patent Document 2] Patent No. 6288382 [Non-patent literature]

[0006] [Non-Patent Document 1] SS Kistler, Nature 1931,127,741. Summary of the Invention [Problem to be solved by the invention]

[0007] As mentioned above, silica-based aerogels have been developed over many years and exhibit a porous structure, resulting in ultra-low thermal conductivity compared to other insulation materials in the world. However, the biggest drawback to applying aerogel is its high manufacturing cost, which limits its uses. An object of the present invention is to provide a method for producing weakly bonded ultrafine aerogel powder that can reduce the production cost per unit occupied volume and has excellent heat insulating properties, a method for producing weakly bonded ultrafine aerogel powder hybridized with hollow particles, and a heat insulating material using the aerogel powder. [Means for solving the problem]

[0008] The inventors conceived the idea that if an aerogel with a very low density is produced, the volume occupied by the same weight can be increased, thereby reducing the production cost, and thus arrived at the present invention. [1] The method for producing the weakly bonded ultrafine particle aerogel powder of the present invention includes, for example, a mixing step of mixing a metal alkoxide with a solvent and hydrolyzing the mixture to produce a sol, a gelling step of gelling the sol obtained in the mixing step, a maturing step of maturing the gel obtained in the gelling step to produce a wet gel, a solvent substitution step of replacing the solvent of the wet gel with a predetermined substitution solvent, a modification step of modifying the surface of the network structure with a predetermined organic group, a step of washing the modified wet gel obtained in the wet gel production step, a step of drying the washed modified wet gel, and a step of pulverizing the dried wet gel. [2] In the method for producing a weakly bonded ultrafine aerogel powder of the present invention, the metal of the metal alkoxide preferably includes at least one of silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), or molybdenum (Mo). [3] In the method for producing weakly bonded ultrafine particle aerogel powder of the present invention, the metal alkoxide is preferably a silicon alkoxide. [4] In the method [3] for producing weakly bonded ultrafine particle aerogel powder of the present invention, it is preferable to use at least one of tetraethoxysilane, trimethoxysilane, tetramethoxysilane, triethoxysilane, tripropoxysilane, tetrapropoxysilane, and tributoxysilane as the silicon alkoxide.

[0009] [5] In the method for producing a weakly bonded ultrafine particle aerogel powder according to the present invention [3], the ratio of the silicon alkoxide to the solvent in the mixing step is preferably within a predetermined range. In the mixing step, an acid catalyst may be added to the solvent to promote the hydrolysis reaction. [6] In the method [3] for producing weakly bonded ultrafine particle aerogel powder of the present invention, it is preferable to add an acid catalyst and a base catalyst to the mixture of the silicon alkoxide and the solvent in the gelation step. [7] In the method [3] for producing a weakly bonded ultrafine particle aerogel powder of the present invention, preferably, in the aging step, the aging temperature is from 15 to 70°C, and the aging time is from more than 0 hour to 24 hours. [8] In the method for producing weakly bonded ultrafine particle aerogel powder of the present invention [3], preferably, in the modification step, the reactive group that modifies the surface of the network structure with an organic group has only one or more of halogen, amino group, imino group, carboxyl group, alkoxyl group, hydroxyl group, alkyl group, phenyl group, fluoride of an alkyl group, and fluoride of a phenyl group. [9] In the method for producing weakly bonded ultrafine particle aerogel powder of the present invention [8], preferably, in the modification step, the compound added as a reagent having a reactive group is hexamethyldisilazane, hexamethyldisiloxane, trimethylchlorosilane, trimethylmethoxysilane, trimethylethoxysilane, triethylethoxysilane, triethylmethoxysilane, dimethyldichlorosilane, dimethyldiethoxysilane, methyltrichlorosilane, ethyltrichlorosilane, acetic acid, formic acid, succinic acid, or methyl chloride.

[10] In the method for producing weakly bonded ultrafine aerogel powder of the present invention [9], preferably, in the wet gel washing step, the wet gel that has been subjected to the modification step is washed with a washing liquid so as to remove the reagent having the reactive group from the gel.

[11] In the method for producing weakly bonded ultrafine aerogel powder of the present invention [3], the drying step is preferably performed under atmospheric pressure.

[12] In the method for producing weakly bonded ultrafine aerogel powder of the present invention [3], preferably, in the pulverization step, the aerogel dried by the method described in

[11] is pulverized so that the weakly bonded ultrafine aerogel contains 50% or more aerogel particles having primary particles as skeletal units, and the remainder is aerogel particles having secondary particles as skeletal units.

[0010]

[13] In the method for producing weakly bonded ultrafine particle aerogel powder of the present invention [3], the solvent in the mixing step is preferably at least one of methanol, ethanol, n-propanol, 2-propanol, n-butanol, 2-butanol, and t-butanol.

[14] In the method for producing weakly bonded ultrafine particle aerogel powder of the present invention [3], the replacement solvent is preferably at least one of the following organic solvents: methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, acetone, methyl ethyl ketone, 1,2-dimethoxyethane, acetonitrile, hexane, toluene, diethyl ether, chloroform, ethyl acetate, tetrahydrofuran, methylene chloride, N,N-dimethylformamide, dimethyl sulfoxide, acetic acid, and formic acid, used alone or in combination of two or more.

[0011]

[15] The method for producing a weakly bonded ultrafine aerogel powder hybridized with hollow particles of the present invention is the method for producing a weakly bonded ultrafine aerogel powder described in [1] or [2], further comprising, between the mixing step and the gelling step, a step of adding hollow particles to a mixture of the metal alkoxide and the solvent in the mixing step.

[16] The method for producing a weakly bonded ultrafine aerogel powder hybridized with hollow particles of the present invention is the method for producing a weakly bonded ultrafine aerogel powder described in any one of [3] to

[14] , further comprising a step of adding hollow particles to the mixture of the silicon alkoxide and the solvent prepared as a silica precursor in the mixing step.

[17] In the method for producing a weakly bonded ultrafine aerogel powder hybridized with hollow particles according to the present invention

[15] or

[16] , the hollow particles preferably include at least one of nanoparticles having an outer diameter of 30 nm to 360 nm and a shell thickness of 7.5 nm to 65 nm, and microparticles having an outer diameter of 1 μm to 23 μm and a shell thickness of 0.35 μm to 3 μm.

[18] In the method for producing a weakly bonded ultrafine particle aerogel powder hybridized with hollow particles according to the present invention

[17] , the amount of the hollow nanoparticles added is preferably 0.01% by weight to 30% by weight based on the total weight of the hybridized aerogel.

[19] In the method for producing a weakly bonded ultrafine particle aerogel powder hybridized with hollow particles according to the present invention

[17] , preferably, the amount of the hollow microparticles added is 0.01% by weight to 30% by weight based on the total weight of the hybridized aerogel.

[0012]

[20] The heat insulating material of the present invention is characterized in that it is made of an aerogel having a three-dimensional network structure whose skeleton is composed of clusters, which are aggregates of primary particles, and contains fine particles having a three-dimensional network structure whose skeleton is composed of the primary particles. Here, the primary particles will be explained. In the three-dimensional network structure of conventional aerogel powder particles, the units that compose the skeleton are called secondary particles (see, for example, paragraph 0033 of Patent Document 1). A primary particle is a smaller unit particle that is formed by gathering a plurality of particles to compose this secondary particle. According to the same document, the diameter of a secondary particle is approximately 2 nm to 50 μm, while the diameter of a primary particle is 0.1 nm to 5 μm. However, as common technical knowledge, there is no universally uniform range for the absolute values ​​of the particle diameters of primary particles and secondary particles.

[21] In the thermal insulation material

[20] of the present invention, the aerogel preferably has a three-dimensional network structure having a skeleton composed of primary particles of a metal oxide, and the metal of the metal oxide is at least one oxide of silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), or molybdenum (Mo).

[22] In the heat insulating material

[20] or

[21] of the present invention, preferably, 50% or more of the total number of the fine particles are dispersed with a mode of particle diameter of 0.1 μm or more and 1.0 μm or less. The particle diameter referred to here is a value observed by a laser diffraction type particle size distribution measuring device. In this specification, laser diffraction type particle size distribution measurement is abbreviated as PSD (particle size distribution) measurement. In this specification, the particle diameter is explained on the premise of PSD measurement. However, in PSD measurement, not only the diameter of the particle itself but also the aggregation of particles is observed as the particle diameter, so that the true particle diameter is likely to be smaller than the measured value. If there is a difference in particle diameter depending on the measurement method, the particle diameter may be appropriately converted and read as such.

[23] In the insulating materials of the present invention

[20] to

[22] , preferably, the insulating material further contains hollow particles.

[24] In the insulating material of the present invention

[23] , the hollow particles preferably include at least one of nanoparticles having an outer diameter of 30 nm or more and 360 nm or less, and microparticles having an outer diameter of 1 μm or more and 23 μm or less.

[25] In the insulating material

[23] or

[24] of the present invention, preferably, the hollow particles have a shell, and a gas having a thermal conductivity lower than that of air is sealed in the hollow part inside the shell. Effect of the Invention

[0013] According to the method for producing the weakly bonded ultrafine aerogel powder of the present invention, it is possible to provide an ultrafine aerogel powder with an expanded volume occupied by the aerogel powder. The expanded volume of the ultrafine aerogel powder allows the same weight to fill a larger volume, thereby reducing the material cost of the heat insulating material. According to the method for producing the hollow particle hybridized weakly bonded ultrafine aerogel powder of the present invention, it is possible to provide an ultrafine aerogel powder containing hollow particles, which can be filled into a larger volume with the same weight, thereby reducing the material cost of the heat insulating material. According to the heat insulating material of the present invention, since ultrafine aerogel powder or weakly bonded ultrafine aerogel powder hybridized with hollow particles is used, the powder size is smaller than that of conventional aerogels, and the unit occupied volume of the aerogel material can be expanded. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a manufacturing process diagram for explaining an example of an aerogel synthesis process, showing the synthesis process of weakly bonded ultrafine aerogel powder. [Diagram 2] FIG. 13 is a sequence diagram illustrating a high-speed crushing process. [Diagram 3] FIG. 1 is an explanatory diagram showing a typical structure of aerogel and aerogel powder produced by pulverizing the aerogel. [Figure 4] FIG. 1 is an explanatory diagram showing a schematic diagram of the aerogel of the present invention and ultrafine aerogel powder produced by pulverizing the aerogel. [Diagram 5] FIG. 1 shows SEM images of a commercially available aerogel and weakly bonded ultrafine aerogel powder. [Figure 6] FIG. 1 shows the particle size distribution of commercially available aerogel and weakly bonded ultrafine aerogel powder. [Figure 7] FIG. 1 is an external view of a weakly bonded ultrafine aerogel powder according to one embodiment of the present invention. [Figure 8] FIG. 1 is a diagram showing the thermal conductivity of commercially available aerogel and weakly bonded ultrafine aerogel powder. [Figure 9] FIG. 1 illustrates the difference in density of aerogel powders under different grinding mechanisms. [Figure 10] 1 shows numerical data of particle size distribution data of weakly bonded ultrafine particle aerogel powder according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Definition> In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In a numerical range described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage may be replaced with the upper limit or lower limit of a numerical range of another stage. In a numerical range described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an example. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. In this specification, the content of each component in the composition means the total amount of multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified.

[0016] <Aerogel> In the narrow sense, a dry gel obtained by using a supercritical drying method on a wet gel is called an aerogel, a dry gel obtained by drying under atmospheric pressure is called a xerogel, and a dry gel obtained by freeze-drying is called a cryogel. In this embodiment, however, a low-density dry gel obtained regardless of the drying method of the wet gel is called an aerogel. That is, in this embodiment, the aerogel means a "gel comprised of a microporous solid in which the dispersed phase is a gas" which is an aerogel in the broad sense. <Aerogel Powder> Aerogel powder is a powder obtained by pulverizing aerogel.

[0017] Hereinafter, each step of the method for producing the weakly bonded ultrafine aerogel powder of this embodiment will be described. Figure 1 is a manufacturing process diagram explaining an example of the synthesis process of aerogel, showing the synthesis process of weakly bonded ultrafine aerogel powder. The synthesis process of weakly bonded ultrafine aerogel powder includes mixing, gelling, aging, solvent replacement, modification, washing, and grinding. Here, silica aerogel is produced through two main processes: formation of a wet gel by sol-gel chemistry and drying of the wet gel. The wet gel is composed of a three-dimensional network skeleton of silica nanostructure formed by hydrolysis and condensation of silica precursor molecules and a liquid solvent. By controlling the parameters of the aging and grinding processes, the volume of the aerogel powder can be expanded.

[0018] (Mixing process) The mixing step is a step of mixing a metal alkoxide (e.g., silicon alkoxide) with a solvent and hydrolyzing the mixture to generate a sol. In the mixing step, an acid catalyst may be added to the solvent to promote the hydrolysis reaction. In the case of a method for producing a weakly bonded ultrafine particle aerogel powder hybridized with hollow particles, the mixing step refers to a step of mixing a metal alkoxide (e.g., silicon alkoxide) with a solvent containing hollow particles and hydrolyzing the mixture to generate a sol.

[0019] The metal alkoxide may contain at least one of the following metal elements: silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), and molybdenum (Mo). The silicon alkoxide may have at least one of a hydrolyzable functional group and a condensable functional group, and may have both a hydrolyzable functional group and a condensable functional group. For example, at least one of tetraethoxysilane, trimethoxysilane, tetramethoxysilane, triethoxysilane, tripropoxysilane, tetrapropoxysilane, and tributoxysilane may be used as the silicon alkoxide.

[0020] Examples of hydrolyzable functional groups include alkoxy groups. Examples of condensable functional groups (excluding functional groups that are hydrolyzable functional groups) include hydroxyl groups, silanol groups, carboxyl groups, and phenolic hydroxyl groups. The hydroxyl groups may be contained in hydroxyl-containing groups such as hydroxyalkyl groups. Each of the hydrolyzable functional groups and the condensable functional groups may be used alone or in combination of two or more types.

[0021] As the solvent, for example, water or a mixture of water and alcohols can be used. Examples of alcohols include methanol, ethanol, n-propanol, 2-propanol, n-butanol, 2-butanol, and t-butanol. Among these, examples of alcohols having low surface tension and low boiling point in terms of reducing the interfacial tension with the gel wall include methanol, ethanol, and 2-propanol. These may be used alone or in combination of two or more. The weight ratio of the solvent to the silicon alkoxide may be, for example, 1 to 1.5 times.

[0022] Examples of the base catalyst include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide; ammonium hydroxide, etc. Among these, ammonium hydroxide (ammonia water) is highly volatile and does not easily remain in the aerogel after drying, so it is less likely to impair water resistance, and is also excellent in terms of economy. The above base catalysts may be used alone or in combination of two or more kinds.

[0023] Examples of the acid catalyst include inorganic acids such as hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, hypophosphorous acid, bromic acid, chloric acid, chlorous acid, hypochlorous acid, etc.; acid phosphates such as acid aluminum phosphate, acid magnesium phosphate, and acid zinc phosphate; and organic carboxylic acids such as acetic acid, formic acid, propionic acid, oxalic acid, malonic acid, succinic acid, citric acid, malic acid, adipic acid, and azelaic acid. Among these, organic carboxylic acids can be mentioned as acid catalysts that further improve the water resistance of the obtained aerogel composite. Examples of the organic carboxylic acids include acetic acid, but may also be formic acid, propionic acid, oxalic acid, malonic acid, etc. These may be used alone or in a mixture of two or more types. The method for producing the weakly bonded ultrafine aerogel powder hybridized with hollow particles will be described in detail later.

[0024] (Gelling process) The gelation step is a step of gelling the sol obtained in the mixing step, followed by aging to obtain a wet gel. In this step, a base catalyst can be used to promote gelation. Examples of the base catalyst include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide; ammonium hydroxide, etc. Among these, ammonium hydroxide (ammonia water) is highly volatile and unlikely to remain in the aerogel after drying, and is also excellent in terms of economy. The above base catalysts may be used alone or in combination of two or more kinds.

[0025] By using a base catalyst, it is possible to promote the dehydration condensation reaction or the dealcoholization condensation reaction of the metal alkoxide in the sol, and the gelation of the sol can be completed in a shorter time. In particular, by using ammonia as the base catalyst, it is possible to easily obtain a weakly bonded ultrafine particle aerogel.

[0026] (ripening process) The aging step may be carried out in a sealed container so that the solvent and the base catalyst do not volatilize. The aging step strengthens the bonds between the components constituting the wet gel, and as a result, a wet gel having sufficient strength to suppress shrinkage during drying can be obtained. Table 1 shows the conditions for the manufacturing process of the weakly bonded ultrafine particle aerogel according to one embodiment of the present invention, and defines the range of variables for the aging process. As shown in Table 1, the aging temperature can be, for example, 15 to 70° C., but is preferably 20 to 70° C., and more preferably 25 to 60° C. By setting the aging temperature at 15° C. or higher, a wet gel with higher strength can be obtained, and by setting the aging temperature at 70° C. or lower, it becomes easier to suppress the volatilization of the solvent (especially alcohols), so that aging can be performed while suppressing volumetric shrinkage. [Table 1]

[0027] The maturation time varies depending on the maturation temperature. In the case of the method for producing a weakly bonded ultrafine aerogel powder hybridized with hollow particles, the maturation time can be particularly shortened compared to the conventional aerogel production method because the hollow particles are contained in the sol. The maturation time can be, for example, 1 second to 24 hours, preferably 1 second to 12 hours, and more preferably 1 to 3 hours. When the maturation time is 1 second to 3 hours, a weakly bonded wet gel is easily obtained, and when it is 3 to 24 hours, a stronger bonded wet gel is easily obtained.

[0028] In the aging step, the aging temperature may be increased within the above ranges and the aging time may be increased within the above ranges in order to increase the density and bond strength of the resulting aerogel, and the aging temperature may be decreased within the above ranges and the aging time may be shortened within the above ranges in order to decrease the density and bond strength of the resulting aerogel composite.

[0029] (Solvent replacement process) The solvent replacement process is a process in which the solvent of the wet gel is replaced with a predetermined replacement solvent. In this case, the replacement efficiency can be improved by heating. Specifically, the replacement solvent may be a solvent with low surface tension when the drying process is performed at a temperature below the critical point of the solvent used for drying under atmospheric pressure.

[0030] In the solvent replacement step, a solvent with low surface tension can be used. A solvent with low surface tension generally has extremely low mutual solubility with water. Therefore, when a solvent with low surface tension is used in the solvent replacement step, various organic solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, acetone, methyl ethyl ketone, 1,2-dimethoxyethane, acetonitrile, hexane, toluene, diethyl ether, chloroform, ethyl acetate, tetrahydrofuran, methylene chloride, N,N-dimethylformamide, dimethyl sulfoxide, acetic acid, and formic acid can be used as the organic solvent. The above organic solvents may be used alone or in combination of two or more. Alternatively, the solvent may be a hydrophilic organic solvent having high mutual solubility in both water and a solvent having a low surface tension. Examples of the hydrophilic organic solvent include methanol, ethanol, 2-propanol, acetone, and methyl ethyl ketone. From the viewpoint of economy, methanol, ethanol, or methyl ethyl ketone may be used.

[0031] (modification process) The modification process involves modifying the surface of the network structure with organic groups, and using the repulsive forces between the organic groups after drying to create a low-density porous structure. An example of an organic compound used in the modification process is TMCS (Trimethylchlorosilane). Details of the modification process are described, for example, in Koji Tajiri's "Research on the preparation of silica aerogel and its modifications, and evaluation of their structures and thermal and mechanical properties" (Doctoral thesis, Nagoya Institute of Technology (2002), pp. 56-73).

[0032] The reactive group that modifies the surface of the network structure with an organic group is preferably a hydrolyzable functional group and a condensable functional group, but is not limited thereto, and may be a reactive group in silicon alkoxide having a hydrolyzable functional group or a condensable functional group, which further has a reactive group different from the hydrolyzable functional group and the condensable functional group (a functional group that does not fall under the hydrolyzable functional group and the condensable functional group). For example, an epoxy group, a mercapto group, a glycidoxy group, a vinyl group, an acryloyl group, a methacryloyl group, and an amino group can be mentioned. The epoxy group may be contained in an epoxy group-containing group such as a glycidoxy group.

[0033] Examples of reactive groups that modify the surface of the network structure with organic groups include halogens, amino groups, imino groups, carboxyl groups, alkoxyl groups, hydroxyl groups, alkyl groups, phenyl groups, fluorides of alkyl groups, and fluorides of phenyl groups. Only one type of these reactive groups may be present, or two or more types may be present. Specific examples of the organic silane compounds include hexamethyldisilazane, hexamethyldisiloxane, trimethylchlorosilane, trimethylmethoxysilane, trimethylethoxysilane, triethylethoxysilane, triethylmethoxysilane, dimethyldichlorosilane, dimethyldiethoxysilane, methyltrichlorosilane, and ethyltrichlorosilane. In addition to these, organic compounds such as carboxylic acids such as acetic acid, formic acid, and succinic acid, and alkyl halides such as methyl chloride can also be used.

[0034] (Cleaning process) In the washing step, the wet gel obtained in the wet gel generating step is washed. The washing can be repeatedly performed using, for example, water or an organic solvent. In this case, the washing efficiency can be improved by heating.

[0035] As the organic solvent, various organic solvents such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, acetone, methyl ethyl ketone, 1,2-dimethoxyethane, acetonitrile, hexane, toluene, diethyl ether, chloroform, ethyl acetate, tetrahydrofuran, methylene chloride, N,N-dimethylformamide, dimethyl sulfoxide, acetic acid, formic acid, etc. The above organic solvents may be used alone or in combination of two or more.

[0036] The amount of water or organic solvent used in the washing step can be an amount that can sufficiently replace the solvent in the wet gel and wash it. The temperature environment in the washing step can be a temperature equal to or lower than the boiling point of the solvent used in washing. For example, when hexane is used, the temperature can be raised to about 30 to 60°C.

[0037] (drying process) In the drying step, the wet gel that has been washed and (if necessary) solvent-substituted as described above is dried, thereby obtaining a weakly bonded aerogel. The drying method is not particularly limited, and known methods such as normal pressure drying, supercritical drying, or freeze drying can be used. Among these, normal pressure drying or supercritical drying can be used from the viewpoint of ease of manufacturing a low-density weakly bonded aerogel. Furthermore, normal pressure drying can be used from the viewpoint of low-cost production. In this embodiment, normal pressure means 0.1 MPa (atmospheric pressure).

[0038] The aerogel of this embodiment can be obtained by drying the wet gel, which has been subjected to solvent replacement and washing, at atmospheric pressure at a temperature below the critical point of the solvent used for drying. The drying temperature varies depending on the type of the replaced solvent. In particular, in consideration of the fact that drying at high temperatures may accelerate the evaporation rate of the solvent and cause large cracks in the gel, the drying temperature can be increased stepwise up to 40 to 150°C, and may be 40 to 120°C. The drying time varies depending on the volume of the wet gel and the drying temperature, but can be 4 to 36 hours. In this embodiment, applying a pressure below the critical point to accelerate the drying within a range that does not impede productivity is also included in normal pressure drying.

[0039] (Crushing process) The pulverization step involves pulverizing the dried aerogel to destroy the secondary particle structure and mechanically reduce it to the primary particle structure, and may be carried out using a pulverizer. A grinding machine is a unit operation for crushing solid materials into small pieces, and there are many types of grinding machines. Grinding machines include grinding mills, crushers, etc. Crushers use rotating blades to crush particles, and can be operated at high or low speeds. High speeds can crush particles into smaller pieces. Low speeds, on the other hand, are suitable for crushing particles that are tightly bound together. Dried aerogel has low thermal conductivity, so there is a high probability that it will become hot due to the heat generated during crushing, so it is a good idea to provide the crusher with a water-cooling mechanism.

[0040] Grinding mills include bead mills, ball mills, and rod mills. A bead mill is a media agitation grinding machine that uses beads to nano-disperse and finely grind powder. Slurry and beads (media) are placed in the grinding chamber (vessel), which rotates at high speed with the agitation mechanism, imparting energy to the beads through centrifugal force, and grinding the material particles through shear stress, frictional force, and impact force. Powders of about 100 to 150 μm in size can be ground to 1 to several μm, and by using microbeads, it is possible to achieve fine particle size down to several nm. A ball mill is a typical grinding machine for obtaining fine particles. In a ball mill, balls, usually made of sand or metal, are packed into a cylinder that rotates at a slight angle or horizontally, and grinding is performed by collisions and friction with the balls. The material to be crushed is placed into one side of the cylinder, and the crushed material is discharged from the other side. Rod mills use rods (metal cylinders) instead of balls as the grinding medium. The material is pulverized by the impact of the rods on the rotating drum (body), which makes it less likely to be over-pulverized compared to ball mills and produces products with a relatively uniform particle size.

[0041] Table 2 shows an example of the conditions for the manufacturing process of weakly bonded ultrafine particle aerogel according to one embodiment of the present invention, and defines the range of variables for the grinding process when a Wonder Crusher WC-3 manufactured by Osaka Chemical Co., Ltd. is used as the fine grinding mill. As shown in Table 2, the range of variables in the pulverization step is preferably 10,000 to 28,000 rpm, more preferably 10,000 to 25,000 rpm, and most preferably 11,000 to 22,000 rpm. The pulverization time is preferably 1 to 120 minutes, more preferably 3 to 60 minutes, and most preferably 5 to 45 minutes. [Table 2] EXAMPLES

[0042] [Embodiment 1] <Weakly bonded ultrafine airgel powder> This embodiment will be described with reference to the manufacturing process diagram shown in FIG. Silica aerogel is mainly produced in two steps: forming a wet gel using the sol-gel method, and drying the wet gel. The wet gel consists of a nanostructured solid silica network and a liquid solvent, and is produced by hydrolyzing and condensing silica precursor molecules. This silica precursor is produced by mixing TEOS (Tetraethoxysilane) and methanol (mixing process). A total of 6.3 g of oxalic acid (0.01 M) is then added to the mixture, followed by 1.5 g of ammonium hydroxide (NH4OH 0.5 M) to form an alcosol, which gels when left at room temperature (gelation step). Following gelation, the alcogels were aged in methanol at 60°C for 3, 6, and 12 hours, respectively (aging step). To prevent complete evaporation of the methanol during the aging step, an excess amount of methanol may be added to the gel. The amount of excess methanol added may be determined taking into account the amount of evaporation of methanol during the aging step, as well as the aging temperature and aging time.

[0043] In the solvent replacement process, to avoid the reverse reaction of the surface modification, the alcogel was immersed in hexane at 60 °C for 10 h, and the hexane-only solvent was replaced with a mixture of hexane and TMCS (Trimethylchlorosilane) to modify the surface. Here, the volume ratio of hexane to TMCS was kept constant at 4. In the modification process, the alcogel was immersed in the mixture of hexane and TMCS at 60 °C for 24 h (modification process). Before drying of the alcogel, the sample was immersed in pure hexane at 60 °C for 6 h to remove the excess TMCS (washing process).

[0044] The final step in creating aerogel is drying (drying process). The drying process consists of steps 1 to 3 and a cooling step, as shown in Table 3 below. The first step was held at 40°C for 4 hours, the second step at 80°C for 2 hours, and the third step at 120°C for 1 hour, and then cooled together with the entire furnace. [Table 3]

[0045] After the drying process, the aerogel sample was subjected to high-speed pulverization (pulverization process). Using a Wonder Crusher WC-3 manufactured by Osaka Chemical Co., Ltd., which corresponds to a fine pulverizer, a program of about 5 minutes at a high speed of 11200 rpm to 21000 rpm was carried out three times, as shown in FIG. 2.

[0046] It should be noted that it is practically difficult to completely distinguish between gelation and aging, and that the aggregation of fine particles proceeds simultaneously with gelation, leading to a reaction similar to that of aging. In this example, the temperature of the alcosol is raised from room temperature to 60°C to promote aging, but in applications where fine particles are preferred, the temperature of the alcosol may be kept at room temperature, and the aging process may be a short process of about 1 second to 1 minute, in which case it may not be clearly distinguishable from the gelation process.

[0047] Next, the weakly bonded ultrafine aerogel powder after high speed crushing according to the present invention will be described. Each ultrafine aerogel powder of the present invention has a three-dimensional network structure. Conventional aerogel powder particles also have a three-dimensional network structure, but the ultrafine aerogel powder of the present invention has a different unit constituting its skeleton. That is, as described in paragraph 0033 of Patent Document 1, "aerogel particle 1 is considered to be in the form of a secondary particle composed of a plurality of primary particles," the three-dimensional network structure of conventional aerogel powder particles is composed of secondary particles as units, whereas the ultrafine aerogel powder of the present invention is characterized in that the unit constituting its skeleton is a primary particle.

[0048] FIG. 3 is an explanatory diagram showing a typical structure of aerogel and aerogel powder produced by pulverizing the aerogel. (A) shows the structure of a typical aerogel 30 and a cut surface 40 obtained when the aerogel is pulverized. (B) shows secondary particles 20 that form the skeleton of the three-dimensional mesh structure. (C) shows aerogel powder 50 produced by pulverizing the aerogel 30 in (A). As shown in FIG. 3(A), in a typical aerogel 30, the colloids contained in the gel before drying become secondary particles 20, and a three-dimensional network structure 30 is formed with the secondary particles 20 as skeleton units. In the aerogel thus created, the skeleton is formed in about 10% of the volume of the three-dimensional network structure, and the remaining 90% is formed by pores. When the size of the pores is smaller than the mean free path of the gas that fills the pores, such as air, almost no heat conduction occurs due to collisions of gas molecules. For this reason, aerogel is used as a thermal insulation material.

[0049] FIG. 3(C) shows a schematic structure of aerogel powder 50 when a general aerogel is crushed. When the general aerogel shown in FIG. 3(A) is crushed, the cut surface 40 by the crusher is not the secondary particles 20 themselves, but the points where the secondary particles are connected. This is thought to be because, as shown in FIG. 3(B), the secondary particles are strongly bonded because the primary particles are densely aggregated, and the bonds between the secondary particles are much weaker. As a result, the aerogel powder 50 when the general aerogel is crushed has a three-dimensional network structure in which the skeleton is formed by the secondary particles 20 (FIG. 3(C)).

[0050] FIG. 4 is an explanatory diagram showing the structure of the aerogel 31 of the present invention and the ultrafine aerogel powder 51 produced by pulverizing the aerogel 31, in which (A) shows the three-dimensional mesh structure of the aerogel 31 generated after the aging process in the process of producing the ultrafine aerogel powder 51 of the present invention, (B) shows secondary particles 21 constituting the skeleton of the three-dimensional mesh structure of the aerogel shown in (A), (C) shows a cut surface 40 when the aerogel 31 shown in (A) is pulverized, and (D) shows the ultrafine aerogel powder 51 of the present invention.

[0051] In the present invention, aerogel is produced by suppressing aging compared to the general process. Therefore, the three-dimensional network structure of the produced aerogel 31 is formed with the secondary particles 21 (FIG. 4(B)) in which the primary particles 11 are more sparsely packed than in the conventional process (FIG. 4(A)). When ultra-high speed pulverization is performed on an aerogel having such a three-dimensional network structure 31 (FIG. 4(A)), not only the mutual bonding parts of the secondary particles 21 that constitute the skeleton, but also the secondary particles 21 themselves have cut surfaces 40 by the pulverizer as shown in FIG. 4(C), and it is considered that the secondary particles 21 themselves are pulverized. As a result, the ultrafine particle aerogel powder 51 of the present invention has a three-dimensional network structure in which the skeleton is formed by the primary particles 11 as shown in FIG. 4(D). Note that the secondary particles 21 are formed by sparse aggregation of the primary particles 11 as shown in FIG. 4(B), so that the outer edge of the actual secondary particles 21 is unclear, but in FIG. 4(C), the part corresponding to the outer edge is shown by a broken circle to facilitate understanding.

[0052] FIG. 5(A) shows an SEM image of a commercially available aerogel, and FIG. 5(B) shows an SEM image of a weakly bonded ultrafine aerogel powder according to one embodiment of the present invention.

[0053] FIG. 6 is a distribution diagram showing the particle size distribution after the high-speed grinding process. FIG. 10 shows the numerical data of the particle size distribution data of the weakly bonded ultrafine aerogel powder, which is one embodiment of the present invention, shown in FIG. 6. For each sample with an aging time of 3 hours, 6 hours, and 12 hours, the particle size after the high-speed grinding process is plotted on the horizontal axis in a log scale, and the frequency (left vertical axis) and cumulative value (right vertical axis) of the relative particle amount are shown. For comparison, data of a conventional (commercially available) aerogel powder are also shown. Here, the particle size was observed by PSD measurement. More specifically, FIG. 6 shows the results of measurement using a laser diffraction type particle size distribution measuring device SALD-2300 manufactured by Shimadzu Corporation. Note that in PSD measurement, not only the diameter of the particle itself but also the aggregation of particles is observed as the particle diameter, so it is necessary to note that the measured value is biased in the positive direction (there are many errors in which a value larger than the true value is measured). However, as described below, sufficient information has been obtained to explain the characteristics of the weakly bonded ultrafine aerogel powder of the present invention.

[0054] In the conventional aerogel powder, the relative particle amount has only one peak with the average particle diameter of about 300 μm. In contrast, in the weakly bonded ultrafine aerogel powder of the present embodiment, the frequency of the relative particle amount after the high-speed grinding process has a bimodal peak for the samples aged for 3 hours, 6 hours, and 12 hours. In the sample aged for 3 hours, the first peak has an average of 0.32 μm, standard deviation 0.10, the second peak has an average of 21.14 μm, standard deviation 0.14, in the sample aged for 6 hours, the first peak has an average of 0.66 μm, standard deviation 0.15, the second peak has an average of 31.89 μm, standard deviation 0.40, and in the sample aged for 12 hours, the first peak has an average of 0.96 μm, standard deviation 0.13, and the second peak has an average of 38.52 μm, standard deviation 0.21.

[0055] The fact that the peaks are divided into two peaks strongly suggests that there is an essential difference between the particles that make up each peak. If there is no essential change and the diameter of the particles produced changes depending on the aging conditions, it is unlikely that two peaks would appear, even if the position of the peak changes accordingly. Therefore, it is natural to think that the particles that make up the second peak, which has a large particle size, have a three-dimensional network structure with secondary particles as the skeleton unit as in the past, while the particles that make up the first peak, which has a small particle size, have a three-dimensional network structure with primary particles as the skeleton unit. In other words, this result supports the explanation above with reference to Figures 3 and 4.

[0056] It can also be seen that by changing the aging conditions, the properties of the particles generated after high-speed grinding, i.e., whether the secondary particles or primary particles are the structural units of the skeleton, can be significantly changed, i.e., controlled. The mode of the dispersion of the larger particle size is 10 μm or more, and the mode of the dispersion of the smaller particle size is 1 μm or less. In the samples aged for 6 and 12 hours and then high-speed grinding, the cumulative value of the relative particle amount exceeds 50% on the side of the larger particle size peak. The cumulative value of the relative particle amount exceeds 50% on the side of the second peak when the particle size is about 20 μm in the sample aged for 6 hours and then high-speed grinding, and about 40 μm in the sample aged for 12 hours and then high-speed grinding. On the other hand, in the sample aged for 3 hours and then high-speed grinding, the cumulative value of the relative particle amount exceeds 50% on the side of the smaller particle size peak (first peak) when the particle size is about 0.3 μm. From another perspective, in the samples aged for 6 and 12 hours and then milled at high speed, 60% to 70% of the particles have a diameter of 10 μm or more, and based on their size, most of the particles have secondary particles as their skeletal building blocks, whereas in the sample of the weakly bonded ultrafine particle aerogel powder of this embodiment aged for 3 hours, approximately 80% of the particles have a diameter in the range of 0.1 μm to 1.0 μm, that is, most of the particles have primary particles as their skeletal building blocks.

[0057] FIG. 7 is an image for explaining the bulk of the weakly bonded ultrafine aerogel powder of this embodiment, showing a case where an aerogel weighing 5 g is placed in a beaker with a capacity of 200 cc or 500 cc. From the left, commercially available aerogel and ultrafine aerogel powder samples with aging times of 12 hours, 6 hours, and 3 hours are shown. The ultrafine aerogel powder samples are those explained in FIG. 6. When the aging time is short, at 3 hours, the bulk of the ultrafine aerogel powder increases to more than 10 times that of the commercially available aerogel.

[0058] Figure 8 is a graph comparing the thermal conductivity of commercially available aerogel and weakly bonded ultrafine aerogel powder. The thermal conductivity of commercially available aerogel granules is 20 [mW / mK]. In contrast, the thermal conductivity of the weakly bonded ultrafine aerogel, which is one embodiment of the present invention, is 23 [mW / mK].

[0059] FIG. 9 shows the difference in density of aerogel powder in different crushing mechanisms, showing a high-speed crusher and ball milling as an embodiment of the present invention, and a low-speed crusher as a comparative example. As shown in Figure 9, the density in the high-speed grinder is 0.0179 g / cm 3 The density measured by ball milling was 0.0548 g / cm 3 The density measured with the low-speed grinder was 0.0790 g / cm 3 In other words, the bulk density of the ultrafine aerogel powder can be reduced by pulverizing the powder using a high-speed pulverizer. [Embodiment 2]

[0060] <Weakly bonded ultrafine aerogel powder with hollow particles added> Hollow particles may be further added to the ultrafine aerogel powder of the above embodiment 1. This can reduce the thermal conductivity of the heat insulating material. By using aerogel as a thermal insulation material, the size of the pores in the aerogel is smaller than the mean free path of air, so that heat conduction through the gas due to collisions of gas molecules or convection is suppressed, and thermal insulation performance close to that when the pores are a vacuum is expected. However, in reality, the performance does not reach that of a vacuum. As a result of the inventor's investigation into the cause, it was found that fine interconnected pores remain in the insulation material filled with aerogel powder, and the above-mentioned heat conduction occurs through these interconnected pores. Therefore, the inventors created a technology to reduce the thermal conductivity by adding hollow particles to the aerogel to hybridize it (patent application filed as Patent Application 2020-120921). The added hollow particles block the fine interconnected pores as described above, suppressing the slight heat conduction through the gas, and therefore the thermal conductivity can be reduced.

[0061] In addition, since the spherical shells constituting the hollow particles are highly airtight, the thermal conductivity of the insulating material can be further reduced by sealing a gas with a lower thermal conductivity than air inside the spherical shells. The hollow particles to be added are not particularly limited, but may be nano-hollow particles, micro-hollow particles, or both. The nano-hollow particles are preferably prepared to have an outer diameter of 30 nm or more and 360 nm or less, and a shell thickness of 7.5 nm or more and 65 nm or less. The outer diameter corresponds to a range of about 1 / 2 to about 5 times the mean free path of air at room temperature and normal pressure. In this way, the hollow size of the nano-hollow particles is prepared to be on the same order as the mean free path of air, so when added to an aerogel, it contributes greatly to the heat insulating effect. The micro-hollow particles are preferably prepared to have an outer diameter of 1 μm or more and 23 μm or less, and a shell thickness of 0.35 μm or more and 3 μm or less. The outer diameter is larger than 15 times the mean free path of air at room temperature and normal pressure, and in addition to contributing to the heat insulating effect, it has the effect of increasing the structural strength of the mesh. The fine interconnected pores described above remain in the aerogel, but the added hollow particles block these pores and suppress heat conduction through gas, such as convection, which occurs through the interconnected pores, thereby improving the insulating effect.

[0062] Hollow nanoparticles can be produced, for example, by the soft template method. That is, the surface of a polymer electrolyte is modified with ammonia in ethanol and then coated with silica (SiO2) to produce particles consisting of a core and a spherical shell. The medium trapped in the core is removed by washing or baking the particles, and hollow particles are produced. For example, the double emulsion method is suitable for producing hollow microparticles. From a dispersed multiphase system consisting of an immiscible liquid such as an oil phase containing a surfactant and an aqueous phase consisting of a precursor and a surfactant, an emulsion containing droplets with the oil phase as the continuous phase and the aqueous phase as the center is produced by emulsification, and by adding aqueous phase to this, it is changed to an emulsion containing droplets with the gel as the center in the aqueous phase continuous phase. By washing / filtering or baking this, hollow microparticles are produced.

[0063] In the method for producing ultrafine aerogel powder of the present invention, the hollow particles are preferably added to a mixture of TEOS and methanol prepared as a silica precursor (mixing step) before the gelation step in the manufacturing process diagram shown in Figure 1. After the addition, the mixture is sufficiently stirred by ultrasonic vibration to uniformly disperse the added hollow particles. The amount of hollow particles added is adjusted to have the following composition with respect to the entire hybridized aerogel.

[0064] The content of the hollow nanoparticles is preferably 0.01% to 30% by weight, more preferably 0.10% to 15% by weight, and most preferably 1.00% to 10% by weight. Similarly, the content of the hollow microparticles is preferably 0.01% to 30% by weight, more preferably 0.10% to 15% by weight, and most preferably 1.00% to 10% by weight.

[0065] As shown in the second embodiment, the thermal conductivity of the heat insulating material can be reduced by adding hollow particles to the ultrafine aerogel powder.

[0066] In the embodiment of the method for producing weakly bonded ultrafine aerogel powder or the method for producing weakly bonded ultrafine aerogel powder hybridized with hollow particles of the present invention, a case of producing silica aerogel powder is shown, but the present invention is not limited to the case of using silicon aerogel as the metal aerogel, and various metal elements, that is, silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), or molybdenum (Mo) may be used as a metal oxide aerogel containing at least one of them. In addition, in the embodiment of the heat insulating material of the present invention, a case where silica aerogel powder is used has been shown, but the present invention is not limited to the case where silicon aerogel is used as the metal oxide aerogel, and various metal elements, that is, at least one of aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), or molybdenum (Mo) may be used. [Industrial Applicability]

[0067] The method for producing weakly bonded ultrafine aerogel powder of the present invention is suitable for use in producing weakly bonded ultrafine aerogel powder. Also, the method for producing weakly bonded ultrafine aerogel powder hybridized with hollow particles of the present invention is suitable for use in producing weakly bonded ultrafine aerogel powder hybridized with hollow particles. The method for producing the weakly bonded ultrafine aerogel powder of the present invention is suitable for use as a heat insulating material. The weakly bonded ultrafine aerogel powder to which hollow particles are added of the present invention is also suitable for use as a heat insulating material. [Explanation of symbols]

[0068] 11 Primary particles 20 Secondary particles 21 Secondary particles formed by sparsely packing primary particles 30 Three-dimensional network structure formed by a skeleton of secondary particles 31 A three-dimensional network structure formed by a skeleton of secondary particles that are sparsely packed together by primary particles 40 Cut surface by crusher 50 General Aerogel Powder 51 Ultrafine aerogel powder of the present invention

Claims

1. a mixing step of mixing a metal alkoxide with a solvent and hydrolyzing the mixture to form a sol; a gelling step of gelling the sol obtained in the mixing step; an aging step of aging the gel obtained in the gelation step to obtain a wet gel; A solvent replacement step of replacing the solvent of the wet gel with a predetermined replacement solvent; a modification step of modifying the surface of the network structure with a predetermined organic group; a step of washing the modified wet gel obtained by sequentially undergoing the mixing step, the gelling step, the aging step, the solvent replacement step, and the modification step; drying the washed modified wet gel; crushing the dried wet gel to destroy the secondary particle structure and mechanically reduce it to a primary particle structure; A method for producing a weakly bonded ultrafine particle aerogel powder comprising the steps of:

2. The metal of the metal alkoxide is at least one of silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), or molybdenum (Mo). The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 1.

3. the metal alkoxide is a silicon alkoxide; 2. The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 1, wherein an acid catalyst and a base catalyst are added to the mixture of the silicon alkoxide and the solvent in the gelation step.

4. the metal alkoxide is a silicon alkoxide; 2. The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 1, wherein in the aging step, the aging temperature is 15 to 70° C., and the aging time is more than 0 hours and less than 24 hours.

5. the metal alkoxide is a silicon alkoxide; 2. The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 1, wherein in the modification step, the reactive group that modifies the surface of the network structure has one or more of halogen, amino group, imino group, carboxyl group, alkoxyl group, hydroxyl group, alkyl group, phenyl group, alkyl fluoride, and phenyl fluoride.

6. In the modification step, the compound added as a reagent having the reactive group is hexamethyldisilazane, hexamethyldisiloxane, trimethylchlorosilane, trimethylmethoxysilane, trimethylethoxysilane, triethylethoxysilane, triethylmethoxysilane, dimethyldichlorosilane, dimethyldiethoxysilane, methyltrichlorosilane, ethyltrichlorosilane, acetic acid, formic acid, succinic acid, or methyl chloride. The method for producing weakly bonded ultrafine particle aerogel powder according to claim 5.

7. 7. The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 6, wherein the wet gel washing step includes washing the wet gel that has been subjected to the modification step with a washing liquid so as to remove the reagent having the reactive group from the gel.

8. the metal alkoxide is a silicon alkoxide; 2. The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 1, wherein the drying step is carried out under atmospheric pressure.

9. 9. The method for producing a weakly bonded ultrafine aerogel powder according to claim 8, wherein the pulverization step pulverizes the aerogel so that 50% or more of the aerogel particles have primary particles as skeleton units in the weakly bonded ultrafine aerogel, and the remainder are aerogel particles having secondary particles as skeleton units.

10. The method for producing a weakly bonded ultrafine particle aerogel powder according to claim 1, further comprising: a step of adding hollow particles to the mixture of the metal alkoxide and the solvent in the mixing step between the mixing step and the gelling step; A method for producing weakly bonded ultrafine aerogel powder hybridized with hollow particles.

11. The method for producing a weakly bonded ultrafine particle aerogel powder according to any one of claims 3 to 9, further comprising: Between the mixing step and the gelling step, a step of adding hollow particles to the mixed liquid of the silicon alkoxide and the solvent prepared as a silica precursor in the mixing step is included. A method for producing weakly bonded ultrafine aerogel powder hybridized with hollow particles.

12. The hollow particles are A hollow nanoparticle having an outer diameter of 30 nm or more and 360 nm or less and a shell thickness of 7.5 nm or more and 65 nm or less; At least one of hollow microparticles having an outer diameter of 1 μm or more and 23 μm or less and a shell thickness of 0.35 μm or more and 3 μm or less, A method for producing a weakly bonded ultrafine particle aerogel powder hybridized with the hollow particles according to claim 10 or 11.

13. An insulating material characterized in that it uses aerogel as a raw material, which has a three-dimensional mesh structure whose skeleton is composed of secondary particles, which are an aggregate of primary particles, and contains fine particles having a three-dimensional mesh structure whose skeleton is composed of primary particles generated by destroying the secondary particles.

14. 14. The thermal insulation material according to claim 13, wherein the primary particles are a metal oxide, and the metal of the metal oxide is at least one oxide of silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), hafnium (Hf), yttrium (Y), vanadium (V), cerium (Ce), lanthanum (La), neodymium (Nd), samarium (Sm), praseodymium (Pr), holmium (Ho), or molybdenum (Mo).

15. The insulating material according to claim 13, characterized in that in the particle size distribution of the microparticles, 50% or more of the total number of particles are distributed in the particle size range of 0.1 μm or more and 1.0 μm or less, and the mode is within said particle range.

16. The insulation material of claim 13, further comprising hollow particles.

17. The heat insulating material according to claim 16, wherein the hollow particles include at least one of nano-hollow particles having an outer diameter of 30 nm or more and 360 nm or less, and micro-hollow particles having an outer diameter of 1 μm or more and 23 μm or less.

18. 17. The heat insulating material according to claim 16, wherein the hollow particles have a shell, and a gas having a thermal conductivity lower than that of air is sealed in the hollow portion inside the shell.

Citation Information

Patent Citations

  • Preparation method of light hydrophobic heat preservation and fireproofing methyl azo color aerogel coating

    CN109722067A

  • Coil and coil bobbin for motor or generator and manufacture of coil

    JP1980023788A

  • JP1980500614A

  • Electrostriction effect element

    JP1987088382A

  • Production of fine silica particles

    JP1990255517A